Antiviral drug-induced nephrotoxicity. - Neto, Ricardo (2007)
Antiviral drug-induced kidney injury, frequently leading to acute renal failure, is increasing in incidence. We review the pathogenesis and clinical manifestations of antiviral drug-induced nephrotoxicity, as well as strategies for prevention and treatment.